2004
DOI: 10.1007/s00221-004-1899-9
|View full text |Cite
|
Sign up to set email alerts
|

Unifying multisensory signals across time and space

Abstract: The brain integrates information from multiple sensory modalities and, through this process, generates a coherent and apparently seamless percept of the external world. Although multisensory integration typically binds information that is derived from the same event, when multisensory cues are somewhat discordant they can result in illusory percepts such as the "ventriloquism effect." These biases in stimulus localization are generally accompanied by the perceptual unification of the two stimuli. In the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

55
287
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(343 citation statements)
references
References 17 publications
55
287
1
Order By: Relevance
“…The second key aspect of this task which must be included in any full generative model of this problem is that oddity can be entailed in the probe stimulus not only by its combined difference from the standard, but by discrepancy within the probe stimulus. In this case (similar to other recent multisensory perception experiments with variable causal structure : Hairston et al, 2003;Shams et al, 2000Shams et al, , 2005Wallace et al, 2004), the variable structure can effectively "give away" the probe. We introduced the approach needed to solve this type of problem in multisensory perception as structure inference (Hospedales & Vijayakumar, 2008).…”
Section: Modeling Oddity Detectionsupporting
confidence: 74%
See 3 more Smart Citations
“…The second key aspect of this task which must be included in any full generative model of this problem is that oddity can be entailed in the probe stimulus not only by its combined difference from the standard, but by discrepancy within the probe stimulus. In this case (similar to other recent multisensory perception experiments with variable causal structure : Hairston et al, 2003;Shams et al, 2000Shams et al, , 2005Wallace et al, 2004), the variable structure can effectively "give away" the probe. We introduced the approach needed to solve this type of problem in multisensory perception as structure inference (Hospedales & Vijayakumar, 2008).…”
Section: Modeling Oddity Detectionsupporting
confidence: 74%
“…That is, it was not obvious which of multiple possible sources caused the observations (Hairston et al, 2003;Shams, Kamitani, & Shimojo, 2000;Shams, Ma, & Beierholm, 2005;Wallace et al, 2004), or which of multiple possible world models was true (Knill, 2007). In these cases, the standard MLI linear-cue-combination approach fails to explain human performance.…”
Section: Multisensory Oddity Detection As Bayesian Inferencementioning
confidence: 99%
See 2 more Smart Citations
“…Research with human adults and animals has shown that when (and when not) stimuli to different sense modalities originate from a common location in external space, this has important implications for neural processing and behaviour (e.g., Meredith & Stein, 1996;Stein & Stanford, 2008;Spence & Driver, 2004;Wallace, Roberson, Hairston, Stein, Vaughan, & Schirillo, 2004). Adults perceive and make use of spatial commonalities across the senses in a seemingly effortless manner.…”
Section: Visual-tactile Co-location In Infantsmentioning
confidence: 99%